Habitat Loss and Avian Range Dynamics through Space and Time - Desrochers, Rachelle (Université d'Ottawa / University of Ottawa, 2011)
The species–area relationship (SAR) has been applied to predict species richness declines as area is converted to human-dominated land covers.In many areas of the world, however, many species persist in human-dominated areas, including threatened species. Because SARs are decelerating nonlinear, small extents of natural habitat can be converted to human use with little expected loss of associated species, but with the addition of more species that are associated with human land uses. Decelerating SARs suggest that, as area is converted to human-dominated forms, more species will be added to the rare habitat than are lost from the common one. This should lead to a peaked relationship between richness and natural area. I found that the effect of natural area on avian richness across Ontario was consistent with the sum of SARs for natural habitat species and human-dominated habitat species, suggesting that almost half the natural area can be converted to human-dominated forms before richness declines. However, I found that this spatial relationship did not remain consistent through time: bird richness increased when natural cover was removed (up to 4%), irrespective of its original extent. The inclusion of metapopulation processes in predictive models of species presence improves predictions of diversity change through time dramatically. Variability in site occupancy was common among bird species evaluated in this study, likely resulting from local extinction-colonization dynamics. Likelihood of species presence declined when few neighbouring sites were previously occupied by the species. Site occupancy was also less likely when little suitable habitat was present. Consistent with expectations that larger habitats are easier targets for colonists, habitat area was more important for more isolated sites. Accounting for the effect of metapopulation dynamics on site occupancy predicted change in richness better than land cover change and increased the strength of the regional richness–natural area relationship to levels observed for continental richness–environment relationships suggesting that these metapopulation processes “scale up” to modify regional species richness patterns making them more difficult to predict. It is the existence of absences in otherwise suitable habitat within species’ ranges that appears to weaken regional richness–environment relationships.
Keywords: Species richness; Ontario Breeding Bird Atlas; Habitat loss; Metapopulation dynamics; Avian distributions; Species-area relationship